Vida Saludable: ¿Esta en Riesgo de Deshidratación? - Jennifer Hillan (EDIS)
FCS-8847-Span, a 1-page fact sheet by Jennifer Hillan, is the Spanish version of "Healthy Living: Are You at Risk of Dehydration?" (FCS8847). It provides a short quiz that users can take to find out if they are at risk for dehydration and subsequent problems. Published by the UF Department of Family, Youth and Community Sciences, June 2007.